Revisiting pornography laws: a comparative study between Malaysia and Indonesia / Adli Shamsuddin, Eliya Hamizah Halim and Suraya Azizah Nasaruddin - Shamsuddin, Adli; Halim, Eliya Hamizah; Nasaruddin, Suraya Azizah (2011)
This project paper focuses on the topic of pornography. To start with, pornography has been a controversial topic since decades ago. The debate on pornography constantly questions a person's freedom of expression against morality. Pornography is an international problem, faced by many countries and unfortunately, Malaysia is not exempted from the problem. Worse, there are only three provisions on pornography in Malaysia in the statutes and none of the provisions define the term 'pornography'. Instead, the term 'obscene' is used. Therefore, this project paper also studies what amounts to 'obscene' and is the term interchangeable to the term 'pornography'. Besides, this project paper contains a comparative study on the existing laws relating to pornography between Malaysia and Indonesia. This research scrutinizes the existing laws governing pornography in Malaysia, which can be found under the Penal Code, the Film Censorship Act 2002 and the Communications and Multimedia Act 1998. Meanwhile in Indonesia, the pornography matters are covered under a specific statute known as the Indonesia's Pornography Act 2008. This research continues by analysing the weaknesses and strengths of laws of pornography which exist in both countries. To assist our research, interviews with experts and a further reading on magazines, articles, books and scholarly journals relating to pornography have been conducted. This paper concludes with the research being successful in meeting our objectives. In a nutshell, from our research, the existing pornography laws in Malaysia are in fact sufficient at the moment and there is no need to have a specific Pornography Act as yet.